HIGHER MATERNAL EDUCATION AND NON-WORKING MOTHER AS A STRONG DETERMINANT OF HIGHER MATERNAL LEVEL OF KNOWLEDGE ON IRON SUPPLEMENTATION IN BANTUL DISTRICT, YOGYAKARTA, INDONESIA - Hastrin Hositanisita; Farah Annisa Mardhiyah; Sintha Dewi Purnamasari; Yulinda Kurniasari (Ikatan Sarjana Gizi Indonesia (ISAGI), 2023)
In Indonesia, maternal anemia, which affects nearly half of pregnant women, is still a growing nutritional issue. Several negative impacts of maternal anemia have been validated, including its effect on their offspring such as low birthweight and risk of being stunting. Maternal knowledge affects maternal compliance on iron supplementation consumption which significantly correlated with maternal anaemia status. This study aimed to investigate determinants of maternal knowledge on iron supplementation. A total of 121 pregnant women from Pajangan Sub-District in Bantul participated in this cross-sectional study. A bivariate and multivariate analysis conducted to investigate the correlations of each independent variable to the outcome. The crude and adjusted OR showed that higher mothers’ education level (AOR=3.77, CI=1.184 – 11.98), unemployeed mothers (AOR =2.99, CI = 1.02 – 8.77) and non-anaemic mothers (AOR=5.14, CI=1.51 – 17.45) associated significantly with higher iron supplementation knowledge. Maternal pregnancy status (gravidity and age of pregancy) as well as family income were not associated with maternal knowledge. Information regarding iron supplementation enhancer, inhibition and side effects should be promoted more among mothers. Health practitionaires should also provide health promotion at the workspace to reach employeed mothers in improving healthy pregnancy literacy.